Is Potimirim potimirim (Crustacea, Decapoda, Atyidae) a protandric hermaphrodite species? Behavioral and morphological aspects of the reproductive system - Machado, Marina [UNESP]; Salti, Fernanda Cristina [UNESP]; Bertini, Giovana [UNESP]; Zara, Fernando José [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP] (Elsevier, 2021)
We evaluated the mating behavior of Potimirim potimirim in the laboratory based on the assumption that this caridean might be hermaphroditic. We also performed histology and scanning electron microscopy analyses of the reproductive system of females, males, and differentiated individuals. The mating experiments produced three behavioral stages, namely, interaction, lateral positioning, and copulation (which did not necessarily occur in this sequence). The hypothesis of a random pure searching mating was corroborated by the lack of male courtship, postcopulatory guarding, and the high aggregation of individuals. Three macroscopic ovarian stages were recorded in adult females: rudimentary, developing and mature. Secondary vitellogenesis begins at the developing stage, producing mature yolk. The male reproductive system is formed by testes and the vasa deferentia (VD), that is divided into three regions: proximal, middle, and distal. The proximal VD has a typhlosole that produces a thin layer of type II secretion around the central spermatozoa mass immersed in a type I secretion. External and adherent type III secretion is produced from the MVD to DVD, and both compound the primordial spermatophore. Potimirim potimirim has a gonochoric reproductive system and mating behavior and its sexual system does not fit into any of the previously described protandric systems.
Keywords: Freshwater; Gonochorism; Histology; Mating; Sexual system